Exploring Pathways Towards Conflicts Prevention and Resolution Mechanisms and Reconciliation Strategies in West Africa - Saliou Dione; Bakaye Togola (Britain International for Academic Research (BIAR) Publisher, 2023)
This article explores pathways towards conflicts prevention and resolution mechanisms and reconciliation strategies in West Africa with Mali as a case study. Relying on traditional and modern mechanisms and strategies, it explores the rich values and traditions of conflict resolution and peace-building processes used by the Malian government and communities to settle the prevailing conflicts and build a sustainable peace. Indeed, The traditional Malian society was woven together by diverse forms of mutual assistance and solidarity across established families, lineages and clans. That form of social and cultural organization permitted them to prevent and resolve conflicts. To make peace, the Malians need to rely on those ancient values that represented solid foundations to building a strong and peaceful society. This paper further brings to light the modern mechanisms and reconciliation strategies of peacemaking and peacebuilding using the conflict theories of Karl Max and Ludwig Gumplowicz, postcolonialism, and African feminism with the role of women in that process.